High conductivity and high strength Mg–Zn–Cu alloy. (June 2014) - Pan, H.; Pan, F.; Wang, X.; Peng, J.; She, J.; Zhao, C.; Huang, Q.; Song, K.; Gao, Z.
Abstract : In the present work, electrical conductivity (EC) and Vickers hardness of Mg–Zn– x Cu ( x  = 0, 0·5, 1·0 and 1·5) alloys in as cast, as solution and aged states have been investigated. The result shows that the EC of both as cast and as solution samples increases with Cu content, and Cu addition would have remarkably enhanced effect on EC and age hardening response during subsequent aging treatment. The 1·0Cu alloy aged at 160°C for 16 h after solution treatment had the optimal combined properties of high microhardness (94 HV) and high EC value (19·1, 10 6 S m −1 ), noting that the EC of pure Mg is 22·8 (10 6 S m −1 ). It is believed that the accelerated precipitation process for Cu containing alloy is attributed to the favourable interactions between Zn, Cu and vacancies. The microstructure associated with the improvement of EC and microhardness for Cu containing alloy is also discussed in detail.